Dermatoglyphic Assessment in Male Down Syndrome - Parveen, Rehana; Rahman, Md Shamsur; Ahmed, Mahmuda; Azim, Md Ashraful; Momena, Zeenatul; Salman, Mohammad Nahid (Community Based Medical Journal, 2022)
Down syndrome (DS) is the most common chromosomal disorder which causes intellectual disability. It is mainly because of the presence of extra copy of chromosome number 21. Dermatoglyphic has been well established as a diagnostic aid in number of diseases having hereditary basis. Dermatoglyphic data was obtained by the use of ink and prints on a paper. This cross-sectional, analytical type of study was performed at the Department of Anatomy, Dhaka Medical College, Dhaka from January 2017 to December 2017 on 40 Down syndrome subjects (age ranged from 6 to 16) selected from Society for the Welfare of the Intellectually Disabled, Bangladesh (SWID, Bangladesh) and Down Syndrome Society of Bangladesh (DSS) and compared with 40 controls for the establishment of comparison between two groups. Dermatoglyphic prints were used to evaluate the difference in „atd‟ „dat‟ „adt‟ angles and pattern intensity between the control and the DS individuals. The results showed that „atd‟ angle was significantly higher (p<0.05) in Down males than the controls. The dactylography study also revealed lower „dat‟ „adt‟ angles (p<0.05) and pattern intensity (p<0.001) in both hands of Down syndrome group. This method is non-invasive and cost effective. The observed changes in the „atd‟ „dat‟ and „adt‟ angles plus the patterns intensity in the dermatoglyphic study proved that this simple technique could be a valuable tool for selecting individuals of DS for cytogenetic analysis. CBMJ 2022 July: vol. 11 no. 02 P: 144-151